Optimasi Pencarian Jalur dengan Metode A-Star - Veronica Mutiana; Fitria Amastini; Noviana Mutiara (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2013)
High level of traffic density can lead to traffic jam those will make troublesome for driver to reach destination with alternative shortest path on time. Therefore, it is neccessary to make an agent that can choose optimal route without being stuck on traffic jam. In this paper, algorithm for choose optimal route is A* method for shortest path problem and use backtrack process when there is a traffic jam occurs on several roads. The design of algorithm is tested by using data which contain 100 locations or nodes and 158 roads or paths in Gading Serpong with an agent that can searching shortest path and sensor module that can send the traffic status based on number of vehicle on several particular node. Based on testing, A* method does not guarantee for path selection if agent is not full observable with environment and there is some case that can lead a worst case. Index Terms— A* Algorithm, Backtrack, Shortest Path, Traffic Density